Specificity of Being and "Different Modernities" of a Person in the Contextual Range of Anthropological Conflict of Postmodernism - Sergey Kostyuchkov (International Society of Philosophy and Cosmology, 2017)
Specificity studies of human nature in the context of postmodern anthropological impacts on the necessity for use as philosophical and sociocultural approaches. By focusing on the fact that since the status of a person is the basis of modern system of social ideas and values of cultural space, there is a need to constantly update philosophical approaches to consideration of a person, adequate modern socio-cultural reality. The history of civilization is definitely proved, at least for Homo sapiens, the truth about what philosophy is a great teacher, giving invaluable lessons to the thinking of the individual life. It should be emphasized that the formation of new philosophical ideas in the study of a person is determined not only by local problems and contradictions, but also in a wider meaning by scale transformations in the cultural life of society, changes of its intellectual status, upgrading of social interaction models with regard to new civilizations requests. The author turns to the origins, nature and interpretation of the term "postmodern", gives the classic definition of postmodern proposes results of one's own thoughts. The author sees the output in developing models of social adaptation as the most constructive and effective means of application is being implicitly provides specificity of modern humans in the changing conditions of the world. Said specificity is that the subject of modern civilization is the history of much of the world's population as solidarity, integrated and activated in the political, economic, spiritual, cultural and informational interaction subject.